Temperament and Attachment as a Predictor of Romantic Love among Adults - Wahida Anjum (Peshawar Journal of Psychology and Behavioral Sciences, 2016)
Objectives of the present study were to find out the relationship among the composite scores of temperament, attachment and perception of romantic love among adults in Lahore, Pakistan. Urdu translated version of the Structure of Temperament Questionnaire-Compact (Trofimova, 2010), the Revised Adult Attachment Scale (Collins, 1996), and the Perception of Romantic Love Scale (Anjum & Batool) was administered on the N = 500 participants (was justified and calculated online through A-prior sample size (Soper, 2016) with the age range of 19 to 60 (M = 20.06, SD = 5.63). Results showed highly significant positive relationship among the composite scores of temperament, attachment and perception of romantic love. Findings also revealed that the temperament, attachment, education, and the experience of romantic love were the significant predictors of perception of romantic love. Implications of the study were discussed in the cultural context of Lahore, Pakistan.